Public Administration in Italy
XXXIV, 470 p. 13 illus.
Keywords: This book is one of three volumes that provide a systematic overview of public administration, public management and public governance in Italy. This second volume adopts an interdisciplinary approach to introduce readers to the ways in which public administration in Italy has been studied by various disciplines since the conception of the modern Italian state more than 150 years ago, including administrative law, management, economics, psychology, political science and public policy. The book also assesses key traits regarding the training, recruitment and regulation of public employment in Italy, as well as the role of oversight and judiciary bodies in the practice of public servants’ work. Contributors comprise some of the leading historians, political scientists, lawyers, social scientists and public management scholars from Italy, some of whom have also held key posts in the Italian public sector. It will appeal to students and scholars of public administration, public management and public governance, as well as practitioners with an interest in Italy. Edoardo Ongaro is Professor of Public Management at The Open University, UK. Carla Barbati was Professor of Administrative Law at IULM University, Italy and Councillor of State of Italy. Fabrizio Di Mascio is Professor of Political Science at the University of Turin, Italy. Francesco Longo< is Associate Professor of Public and Health Care Management at Bocconi University, and Senior Professor at the SDA Bocconi School of Management, Italy. Alessandro Natalini is Professor of Political Science at LUMSA University, Italy.